(untitled) (AYUSHDHARA, 2022)
Frozen shoulder, the “Peri-arthritis” or “Adhesive Capsulitis” is the problem of shoulder region in which the shoulder capsule, the connective tissue surrounding the gleno-humeral joint of shoulder, becomes inflamed and stiff, greatly restrict motion and cause chronic pain. In Ayurveda there is no direct reference of frozen shoulder. But there are many problems which are related viz “Avabahuka”, “Amsa Shosha”, “Bahushosha”, “Sandhigata Kupita Vata”, Snayu Gata Kupita Vata. Among these Avabahuka has close correlation with frozen shoulder. This disease usually affects the Amsa Sandhi (shoulder joint). Acharya Sushruta and other Acharyas have considered Avabahuka as a Vataja Vikara. Amsa Shosha (wasting of shoulder) can be considered as the preliminary stage of the disease, where loss or dryness of Shleshak kapha from Amsa Sandhi occurs and hampers the movement of the arm. The most common treatment for frozen shoulder is mobility, exercises and Yoga (Asana & Pranayama). Yogic procedures are helpful in removing the stiffness of the joint. Keeping this in mind I am presenting a review article on following exercises (Suksham Vyayama- wrist movement, elbow movement, shoulder movement, neck movement, wall climbing exercise, towel stretch exercise, Chakkichalan), Asanas (Tadasana, Chakkichalanasana, Ardhakatichakrasana, Katichakrasana and Shashankasana) and Pranayama (Kapalbhati, Nadishodhana (Anulom-Vilom), Bhramari) how they help manage or prevent frozen shoulder.